Kerklike tug volgens 1 Korintiërs 5 en 6 - Engelbrecht, J. J. (Hervormde teologiese studies, 1989)
Ecclesiastical discipline according to 1 Cor 5 & 6 According to Paul the believers in Jesus Christ form a community, being in certain aspects completely different from Jews or Gentiles. In order to be what they in principle already are, and for the ultimate benefit of the offenders, ecclesiastical discipline should be applied by this community of believers. The principle is put clear by Paul, but how should it be put into practice in present day circumstances and in each individual case? Do these chapters have any relevance for today’s church?